A review on the current drugs and new targets for obesity - Poojashree, M J; Siddalingaprasad, H S; Swetha, B R; Swamy, Shivukumar (Journal of Applied Pharmaceutical Research, 2020)
Obesity is defined as the condition in which the Body Mass Index (BMI) of an individual is between 25 and 29.5 that is ≥30kg/m2 and is caused by the imbalance management of energy intake and expenditure. Obesity is among the most prevalent diseases in the world and approximately over 10% of the people belong to overweight group in the world and over 5% in India. Currently many drugs are used to treat or to manage obesity. But these drugs also account for several side effects. So there is an extensive need of promising drugs which can control obesity with greater efficacy and economic viability. This review focusses on the current drugs in the market used to treat obesity and also few of the new probable targets to discover drugs